PENGARUH PENGHARGAAN INTRINSIK DAN PENGHARGAAN EKSTRINSIK TERHADAP MOTIVASI KERJA PEGAWAI (Studi pada Balai Besar Wilayah Sungai Pemali Juana Semarang) - Suryandaru Pudyas Moro, 10.05.51.0021; Waruwu, Penunjang (Students Journal of Economic and Management, 2014)
This study aimed to analyze the influence of Award Intrinsic and extrinsic Award to Employee Work Motivation. The population in this study were all employees of the Central River Region Pemali Juana Semarang.Obyek research in this study is the Central River Region Pemali Juana Semarang. Sampling technique using the "census sampling" were 70 respondents in the sample by using a questionnaire method of data collection (questionnaire) to distribute a list of questions to respondents in order to obtain information from the respondents. The data used in this study is primary data is data obtained directly from the original source. Test equipment used in this study to test the validity of the analysis method and tested product moment reliability using Cronbach alpha to examine the magnitude of the partial effect of each independent variable were tested by regression analysis. The results of the research are: (1) Award Intrinsic positive and significant impact on Employee Work Motivation (2) Extrinsic Award and a significant positive effect on employee work motivation.Keywords: intrinsic rewards, extrinsic rewards, and employee motivation